A nationwide postal survey on the perception of Malaysian public healthcare providers on family medicine specialists (PERMFAMS) clinical performance, professional attitudes and research visibility - Chew, Boon How; Md Yasin, Mazapuspavina; Cheong, Ai Theng; A. Rashid, Mohd Radzniwan; Hamzah, Zuhra; Ismail, Mastura; Ali, Norsiah; Bashah, Baizury; Mohd Salleh, Noridah (SpringerOpen, 2015)
Perception of healthcare providers who worked with family medicine specialists (FMSs) could translate into the effectiveness of primary healthcare delivery in daily practices. This study examined perceptions of public healthcare providers/professionals (PHCPs) on FMSs at public health clinics throughout Malaysia. This was a cross-sectional study in 2012-2013 using postal method targeting PHCPs from three categories of health facilities, namely health clinics, health offices and hospitals. A structured questionnaire was developed to assess PHCP’s perception of FMS’s clinical competency, safety practice, ethical and professional values, and research involvement. It consists of 37 items with Likert scale of strongly disagree (a score of 1) to strongly agree (a score of 5). Interaction and independent effect of the independent variables were tested and adjusted means score were reported. The participants’ response rate was 58.0% (780/1345) with almost equal proportion from each of the three public healthcare facilities. There were more positive perceptions than negative among the PHCPs. FMSs were perceived to provide effective and safe treatment to their patients equally disregards of patient’s social background. However, there were some concerns of FMSs not doing home visits, not seeing walk-in patients, had long appointment time, not active in scientific research, writing and publication. There were significant differences in perception based on a respondent’s health care facility (p < 0.0001) and frequency of encounter (p < 0.0001). PHCPs had overall positive perceptions on FMSs across all the domains investigated. PHCPs from different health care facilities and frequency of encounter with FMSs had different perception. Practicing FMSs could improve on the critical service areas that were perceived to be important but lacking. FMSs might need further support in conducting research and writing for publication.